Pengaruh perbedaan mikroorganisme dan suhu pada kandungan serat jerami padi fermentasi - Yanti, Y.; Kawamoto, Y.; Miyagi, T.; Rahmi, B.; Surahmanto, Surahmanto; Purnomoadi, A. (Universitas Sebelas Maret (UNS), 2014)
The aim of this research was to determine the NDF and ADF content of rice strawfermented with several types of microorganism at different temperatures. Rice straw wasobtained from rice fields in Ishigaki District, Okinawa, Japan. The types of microbes usedwere Lactobacillus fermentum, Bacillus subtilis, Bacillus coagulant Saccharomycescerevisiae, and Aspergillus niger. The mainplot was temperature (25, 35, 45°C) and thesubplot was microorganism. Each treatment has 3 replications. There were two groups forcontrols, i.e. the control without molasses and the control with molasses. The rice strawfermented within 3 weeks. The ADF content in all temperature treatments showed that S.cerevisiae and A. niger treatments were higher (P<0.01) than that in other microorganismtreatments. Hemicellulose content in S. cerevisiae and A. niger were tend to lower (P<0.01)compare to others microorganism treatments in all temperature treatments. The lowesthemicelluloses content of fermented rice straw are showed by S. cerevisiae and A. niger at45°C. These finding suggested that the ADF content were high in S. cerevisiae and A. nigertreatments, but showed decrease in hemicellulose and increase in cellulose and lignin.Key words: rice straw, fermentation, ADF, NDF